Screening for MEN 2 with biochemical and genetic markers - Robinson, M. F.; Gagel, Robert F.; Raue, Friedhelm (Medullary thyroid carcinoma, 1992)
The term “multiple endocrine neoplasia type 2” (MEN 2) denotes a genetic syndrome characterized by the independent appearance of benign or malignant changes of several endocrine organs (the thyroid, parathyroid, and adrenal glands) as well as occasional changes of neuronal, muscular, and connective tissue. Despite the large number of variations of these manifestations, three different forms have been identified:1.MEN 2A (Sipple’s syndrome, Sipple 1961), characterized by medullary thyroid carcinoma (MTC) in association with pheochromocytoma and parathyroid hyperplasia.2.MEN 2B, including MTC, pheochromocytoma and mucosal neuromas, and a marfanoid-like habitus (Williams and Pollock 1966).3.MTC-only syndrome, a hereditary MTC without the other components of MEN 2A (Farndon et al. 1986). Whether this represents a separate syndrome or merely a variant of MEN 2A in which the genetic component is modified to delay the onset of all manifestations of the MEN 2A syndrome is not clear.